2023
DOI: 10.3389/fonc.2023.1134884
|View full text |Cite
|
Sign up to set email alerts
|

Combined biology-guided radiotherapy and Lutetium PSMA theranostics treatment in metastatic castrate-resistant prostate cancer

Abstract: BackgroundLutetium-177 [177Lu]-PSMA-617 is a targeted radioligand that binds to prostate-specific membrane antigen (PSMA) and delivers radiation to metastatic prostate cancer. The presence of PSMA-negative/FDG-positive metastases can preclude patients from being eligible for this treatment. Biology-guided radiotherapy (BgRT) is a treatment modality that utilises tumour PET emissions to guide external beam radiotherapy. The feasibility of combining BgRT and Lutetium-177 [177Lu]-PSMA-617 for patients with PSMA-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The authors proposed that biology-guided radiotherapy could be feasible and even associated with PSMA-RLT in patients with PSMA/FDG discordant metastases. 39 Hotta et al 40 retrospectively evaluated the parotid gland uptake visually and quantitatively in the baseline images of 237 patients treated with either 177 Lu-PSMA-617 or 177 Lu-PSMA-I&T. Most patients (92.4%) presented intermediate to high uptake. PSA50, PSA-PFS and OS presented positive correlation with uptake in salivary glands either in a visual or quantitative scale ( P < 0.005), with good interreader reproducibility (k = 0.68).…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors proposed that biology-guided radiotherapy could be feasible and even associated with PSMA-RLT in patients with PSMA/FDG discordant metastases. 39 Hotta et al 40 retrospectively evaluated the parotid gland uptake visually and quantitatively in the baseline images of 237 patients treated with either 177 Lu-PSMA-617 or 177 Lu-PSMA-I&T. Most patients (92.4%) presented intermediate to high uptake. PSA50, PSA-PFS and OS presented positive correlation with uptake in salivary glands either in a visual or quantitative scale ( P < 0.005), with good interreader reproducibility (k = 0.68).…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
“…Gaudreault et al 39 evaluated 6 patients that were excluded from the LuPSMA trial with a total of 89 PSMA-negative/FDG-positive targets identified. Median gross tumor volume (GTV) of 4.3 cm 3 , and median SUV max of 4.8 were found in 18 F-FDG PET/CT.…”
Section: Psma Radioligand Therapy In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some reports have shown promising results in the treatment of PCLM patients using 177Lu-PSMA radioligand therapy (Lu-PRLT)[ 31 , 32 ]. However, PCLM patients who are PSMA(-)/fluorescein Di-β-D-galactopyranoside (FDG)(+) may not benefit from Lu-PRLT[ 33 ]. Therefore, some researchers have combined biologically guided radiation therapy with Lu-PRLT for PSMA(-)/FDG(+) PCLM patients and found this combination therapy to be beneficial[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, PCLM patients who are PSMA(-)/fluorescein Di-β-D-galactopyranoside (FDG)(+) may not benefit from Lu-PRLT[ 33 ]. Therefore, some researchers have combined biologically guided radiation therapy with Lu-PRLT for PSMA(-)/FDG(+) PCLM patients and found this combination therapy to be beneficial[ 33 ]. Moreover, there have been case reports suggesting that the combination of stereotactic body radiation therapy and androgen deprivation therapy (ADT) can confer benefits in terms of biochemical response and disease-free survival in PCLM patients[ 34 ].…”
Section: Discussionmentioning
confidence: 99%